2014
DOI: 10.11648/j.ijema.20140205.19
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Temporal Changes in Nitrous Oxide Emission with Fertilizer Application in Rice Ecosystem of North Bank Plain Agroclimatic Zone of North East India

Abstract: Fertilizer dosage can influence nitrous oxide (N 2 O) emissions in rice (Oryza sativa L.) fields. An experiment was conducted to find out the temporal and seasonal variations in N 2 O emissions under different doses of fertilizers and to identify the best fertilizer combination for lower N 2 O emission and adequate yield potential. Two rice varieties Phorma (local cultivar) and Luit (high yielding variety) were grown, with nine different fertilizer treatments. N 2 O fluxes were measured by a closed chamber tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Gogoi [52] studied the seasonal and temporal variations associated with N 2 O emissions under different regimes (doses) of fertilizer and also sought to identify the best combination for fertilizer application which can reduce N 2 O emissions but give a higher yield potential. Results from the study showed that temporal fluxes were positively correlated to fertilizer application.…”
Section: Optimization Of Fertilizer Applicationmentioning
confidence: 99%
“…Gogoi [52] studied the seasonal and temporal variations associated with N 2 O emissions under different regimes (doses) of fertilizer and also sought to identify the best combination for fertilizer application which can reduce N 2 O emissions but give a higher yield potential. Results from the study showed that temporal fluxes were positively correlated to fertilizer application.…”
Section: Optimization Of Fertilizer Applicationmentioning
confidence: 99%